2018
DOI: 10.1067/j.cpsurg.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreduction for colorectal metastases: liver, lung, peritoneum, lymph nodes, bone, brain. When does it palliate, prolong survival, and potentially cure?

Abstract: Colorectal cancer commonly metastasizes. The liver is the most frequent site of metastases and dominates the length of survival for this disease. As surgical and systemic therapies have become accepted and now are proven to be potentially curative, other sites of metastases have become more clinically relevant in terms of clinical symptoms and influence on survival. Treatment of extrahepatic metastases by surgical and ablative procedures is increasingly accepted and is proving to be effective at palliating sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
137
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 193 publications
(156 citation statements)
references
References 292 publications
(314 reference statements)
3
137
0
2
Order By: Relevance
“…Some studies have shown that the prognosis of gastric cancer with liver and bone metastasis is worse than that of any other subtype of gastric cancer, and the two organs even account for most metastatic sites [34,35]. Interestingly, we nd that similar situation also exist in colorectal cancer, lung cancer, pancreatic cancer, breast cancer and other tumors [36][37][38][39][40].We deem that the liver and bones may have microenvironments conducive to the synthesis and release of CA242 molecules in the ve "CA242 progression-positive tumors" or that the liver and bones enhance metastatic tumor cell growth so that more tumor cells produce more CA242, resulting in elevated levels. Therefore, CA242 may be valuable in predicting the progression of "CA242 progression-positive tumors".…”
Section: Page 14/19supporting
confidence: 56%
“…Some studies have shown that the prognosis of gastric cancer with liver and bone metastasis is worse than that of any other subtype of gastric cancer, and the two organs even account for most metastatic sites [34,35]. Interestingly, we nd that similar situation also exist in colorectal cancer, lung cancer, pancreatic cancer, breast cancer and other tumors [36][37][38][39][40].We deem that the liver and bones may have microenvironments conducive to the synthesis and release of CA242 molecules in the ve "CA242 progression-positive tumors" or that the liver and bones enhance metastatic tumor cell growth so that more tumor cells produce more CA242, resulting in elevated levels. Therefore, CA242 may be valuable in predicting the progression of "CA242 progression-positive tumors".…”
Section: Page 14/19supporting
confidence: 56%
“…There is a very large body of literature comprising single institutional series and multi-institutional retrospective analyses from expert centers that supports this assertion. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]20,[22][23][24][25][26][27][28]32 A recent instrumental variable analysis provides causal estimates of improved survival after liver resection in a population-based cohort. 21 Utilization of liver resection and factors associated with receipt of liver resection for CRCLM in the US population remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Of these patients, 83% of patients have liver metastases. 2 Ultimately, 71% of patients with metastatic disease will die as a result of progression of liver metastases. 3 Liver resection is the only potentially curative therapy for patients with colorectal cancer liver metastases (CRCLM).…”
Section: Introductionmentioning
confidence: 99%
“…About one-fourth of colorectal cancer patients present with liver metastasis at the time of diagnosis, and another 40-50% will develop liver metastasis later on [3][4][5][6]. In the absence of proper treatment, patients with colorectal liver metastatic disease (CRLM) have a very poor survival, with a reported median survival lying between 6-9 months, and even with the best regimens of chemotherapy, the median survival of unresectable disease does not usually exceed 18 months [7]. However, and with the advances that medicine has witnessed over the past few decades, the median survival of CRLM patients has successfully jumped to forty months with the implementation of liver resection [7].…”
Section: Introductionmentioning
confidence: 99%